Compósito odontológico carregado com nanotubos de carbono: caracterização e ensaios biológicos - Ricardo Antonio Alpino Rodrigues (2021)
Carbon nanotubes (CNT) are candidates for the improvement of dental composites. However, the homogenization and aesthetic commitment of CNT' addition are still a challenge. Moreover, heretofore, there is no study investigating compositions capable of inducing tissue responses towards repair. In this sense, this study aimed to incorporate two concentrations of multiple walls CNT (MWCNT), as growth, in a polymeric network. The chemical, mechanical, and biologicals properties of this experimental biomaterials were assessed. A Bis-GMA and TEGDMA (2:1) base was produced with 0%; 0.001%; or 0.01% MWCNT. The composites were assessed using thermogravimetry, infrared spectroscopy with attenuated total reflectance (FTIR-ATR), scanning electron microscopy (SEM), and were also subjected to compression, bending, sorption-solubility tests in accordance with ISO 4049 :2009, color stability, degree of conversion, microhardness and also to antimicrobial assays in S. aureus (ATCC 25193) (halo formation), S. mutans (ATCC 25175) (biofilm adhesion) and biological assays in keratinocytes (HaCat ) (cytotoxicity) and pre-osteoblasts (MC3T3) (differentiation). LED light (470 nm and 800 mW / cm2) was used to light-cure the monomers. According to ANOVA followed by Tukey's post-hoc, adopting a significance level of 5%, the compressive strength was significantly higher for the 0.001% group (125.66 MPa) than control (46.94 MPa). Flexural strength was also more significant in the 0.001% (51.74 MPa) group than the 0.1% group. There was no significant difference in the values of sorption and solubility and color stability between the evaluated groups. The degree of conversion was lower in the groups with NTCPM when compared to the control group, however the Knoop microhardness was higher in the group with the highest concentration of NTCPM and lower in the group with the lowest concentration when compared to the control group. Despite not showing bacterial inhibition halo formation in any of the groups, the groups containing NTCPM showed a decrease in biofilm adhesion when compared to the control group. All groups shown cytotoxicity on HaCat, but the addition of MWCNT favored MC3T3 mineralization over control. It was concluded that both mechanical and biological properties improved with the addition of low concentration of MWCNT (0.001%). The addition of 0.001% MWCNT looks promising for incorporation in dental composites.